2017
DOI: 10.1016/j.jsat.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers to smoking cessation among adults with substance use disorders

Abstract: The majority of adults seeking substance use disorder treatment also smoke. Smoking is associated with greater substance use disorder severity, poorer treatment outcome, and increased mortality among those with substance use disorders. Yet, engaging this population in smoking cessation treatment is a significant challenge. The aim of this study was to examine perceived barriers to smoking cessation among treatment-seeking adults with alcohol or opioid use disorder. Additionally, we examined whether anxiety sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 64 publications
4
20
0
Order By: Relevance
“…Further, the belief that it is more difficult for people in SUD treatment to quit smoking is associated with poorer quit outcomes for these patients . Therefore, it would be important to address barriers and self‐defeating beliefs about quitting smoking held by SUD patients . Having staff work with patients to integrate smoking cessation into treatment plans may be beneficial, as a recent study of 683 patients receiving SUD treatment found that participants who reported that quitting smoking was part of their treatment plan were more likely to quit smoking than participants without quitting as a goal .…”
Section: Discussionmentioning
confidence: 99%
“…Further, the belief that it is more difficult for people in SUD treatment to quit smoking is associated with poorer quit outcomes for these patients . Therefore, it would be important to address barriers and self‐defeating beliefs about quitting smoking held by SUD patients . Having staff work with patients to integrate smoking cessation into treatment plans may be beneficial, as a recent study of 683 patients receiving SUD treatment found that participants who reported that quitting smoking was part of their treatment plan were more likely to quit smoking than participants without quitting as a goal .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, current smokers were asked “When is the best point to stop smoking in drug treatment?” Response options were: “as soon as treatment begins; after six months of treatment; after one year of treatment; never.” This question was included due to the widespread belief among clients that quitting smoking during treatment may increase the chances of alcohol or other drug use relapse, a belief which can affect motivation to quit (McHugh et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Further, smoking cessation is often associated with mental distress. Anxiety, tension, and frustration are some of the self‐reported barriers to smoking cessation 30 . In current dual users, the use of alcohol and other substances may exacerbate their psychological distress and negatively impact quit attempts.…”
Section: Discussionmentioning
confidence: 99%